Duty cycle analysis and thermal simulation for a lightweight disc brake for a regenerative braking system - Shamsul, Sarip
One of the stated advantages of electric vehicles (EVs), and hybrid vehicles (HVs) is their ability to recuperate braking energy. Regenerative braking (RB) would extend the working range of an EV or HV provided that any extra energy consumption e.g. from increased vehicle mass and system losses did not outweigh the saving from energy recuperation, also reduce duty levels on the brakes themselves, giving advantages including extended brake rotor and friction material life, but more importantly reduced brake mass, minimise brake pad wear. The objective of this paper is to define how much braking energy could be absorbed by a regenerative braking system (RBS) on a passenger car, hence defining the duty envelope of the friction brake. This will enable lighter brakes to be designed and fitted with confidence in a normal passenger car alongside a hybrid electric drive. In this paper, a mathematical analysis (MATLAB) is used to analyse the availability of regenerative braking energy during a single stop braking event. Secondly a computer simulation model based on Advanced Vehicle Simulator (ADVISOR) is used to simulate both single stop and drive cycle braking. Based on both sets of results it is shown how much of the total braking energy could be absorbed by the RBS of an example hybrid car in single stop braking and drive cycle braking. Thermal performance is a key factor which is studied using FEA simulations. Ultimately a design method for lightweight brakes suitable for use on any car-sized hybrid vehicle will be developed. Some results from an experimental lightweight brake disc are shown to illustrate the effects of RBS / friction combination in term of weight reduction.